Chemical analysis for asset management of concrete infrastructure. Issue 3 (September 2016) - Ingham, Jeremy; McKibbins, Leo; Barnes, Richard
Abstract : The effective management of reinforced-concrete assets through the asset life cycle requires that they are designed and specified to provide an appropriate level of durability for their intended service life and conditions, constructed to fulfil the requirements of the designer and subsequently maintained efficiently in a fully serviceable condition. A confident understanding of the properties, performance and current condition of the concrete materials used in construction is fundamental to each stage of this process. This understanding is, in no small part, reliant on the accuracy and reliability of the laboratory techniques available for analysing hardened concrete. In co-operation with 11 testing companies, The Concrete Society undertook a laboratory trial of BS 1881-124: Chemical analysis methods for hardened concrete. The trial findings were published in 2014 in the second edition of Concrete Society Technical Report 32, Analysis of Hardened Concrete: a Guide to Test Procedures and Interpretation of Results . The trial findings have cast significant doubt on the accuracy of test methods that are routinely used during condition investigations of concrete structures. This paper examines the implications for design, maintenance and asset management of the UK concrete infrastructure asset stock.